Examining the Role of Personal Identification With the Leader in Leadership Effectiveness: A Partial Nomological Network. (February 2013) - Zhu, Weichun; Wang, Gang; Zheng, Xiaoming; Liu, Taoxiong; Miao, Qing
Although much research has been done on employee collective identification with the organization and the work unit, the role of followers' personal identification with the leader in followers' work outcomes has not been fully examined. Drawing on research on transformational leadership and social identity theory, the authors examined a partial nomological network of personal identification with the leader and its mediating effects. Results show that transformational leadership was positively related to personal identification with the leader, which was significantly associated with followers' innovativeness, affective organizational commitment, and turnover intention. In addition, personal identification with the leader significantly mediated the relationships of transformational leadership with followers' affective organizational commitment and turnover intention. Although personal identification with the leader did not significantly mediate the relationship between transformational leadership and followers' work outcomes, transformational leaders might indirectly increase followers' innovativeness through gaining followers' personal identification.